Description of Tresuncinidactylus wilmienae gen. et sp. n. (Monogenea: Gyrodactylidae), from the gills of the bulldog, Marcusenius macrolepidotus (Peters) from Lake Kariba, Zimbabwe - Přikrylová, Iva; Barson, Maxwell; Shinn, Andrew P (Folia parasitologica, 2021)
The African continent has a rich diversity of fish and amphibians in its inland water systems that serve as hosts for monogeneans of seven genera of the Gyrodactylidae van Beneden et Hesse, 1832. In August 2011, eight gyrodactylid parasites were collected from the gills of two specimens of bulldog, Marcusenius macrolepidotus (Peters), from Lake Kariba, Zimbabwe. Morphometric evaluation and sequencing of 18S rDNA confirmed that the specimens represented a species of a new viviparous genus, Tresuncinidactylus wilmienae gen. et sp. n. The attachment apparatus consists of a single pair of large slender hamuli with prominently flattened roots that are connected by a simple, narrow dorsal bar. The ventral bar is small and possesses a thin lingulate membrane but no evident anterolateral processes. There are 16 marginal hooks of one morphological type, but of three different sizes, with large falculate sickles that are proportionaly equal in length to the length of their handles. The two largest pairs of marginal hooks are positioned closest to the opisthaptoral peduncle, the neighbouring two pairs of medium-sized marginal hook sickles are situated along the lateral margins of the opisthaptor. Four pairs of smallest marginal hooks are positioned along the posterior margin of the opisthaptor. The male copulatory organ consists of a muscular pouch armed with approximately 30 gracile spines. Phylogenetic analyses of partial sequences of the 18S rDNA using Maximum Likelihood and Bayesian Inference placed the new genus within the lineage of solely African genera and suggests Afrogyrodactylus Paperna, 1968, Citharodactylus Přikrylová, Shinn et Paladini, 2017 and Mormyrogyrodactylus Luus-Powell, Mashego et Khalil, 2003 as genera most closely related to the new genus.
Keywords: Bayes Theorem; Bayesova věta; jezera; Trematoda; psi; Zimbabwe; nemoci ryb; Animals; mužské pohlaví; žábry; Dogs; Gills; Lakes; zvířata; fylogeneze; Male; Fish Diseases; Phylogeny